Circulating T Cell Subsets in Type 1 Diabetes - Aldo Ferreira-Hermosillo; Paola Santana-Sánchez; Ricardo Vaquero-García; Manuel R. García-Sáenz; Angélica Castro-Ríos; Adriana K. Chávez-Rueda; Rita A. Gómez-Díaz; Luis Chávez-Sánchez; María V. Legorreta-Haquet (Cells)
Type 1 diabetes (T1D) is a complex disease driven by the immune system attacking the insulin-producing beta cells in the pancreas. Understanding the role of different T cell subpopulations in the development and progression of T1D is crucial. By employing flow cytometry to compare the characteristics of T cells, we can pinpoint potential indicators of treatment response or therapeutic inefficacy. Our study reveals elevated prolactin (PRL) levels in T1D patients, along with a decreased production of key cytokines. Additionally, PD1 appears to play a significant role in T1D. Notably, PRL levels correlate with an earlier disease onset and a specific T cell phenotype, hinting at the potential influence of PRL. These findings highlight the need for further research to identify promising cellular targets for more effective and tailored therapies.